Catalyst-free photoinduced selective oxidative C(sp3)–C(sp3) bond cleavage in arylamines. Issue 9 (26th April 2021) - Zhou, Jingwei; Wang, Songping; Duan, Wentao; Lian, Qi; Wei, Wentao
Abstract : By introducing a polar atom at the γ-position of amine, the site-selective oxidative cleavage of the saturated C–C single bond in arylamines can be easily achieved by simple visible light irradiation with O2  as a benign oxidant and catalyst free. Abstract : Due to the directional nature of sp 3 -hybridized orbitals and the absence of π-orbitals, the oxidative cleavage of the kinetically and thermodynamically stable C(sp 3 )–C(sp 3 ) bond is extremely difficult and remains scarcely explored. In this work, under the double argument of quantum mechanics (QM) computations and meticulous experiments on our well-designed C–C single bond cleavage mechanism, we discovered a means of photoinduced selective oxidative C(sp 3 )–C(sp 3 ) bond cleavage in arylamines, easily achieved by simple visible light irradiation using O2 as a benign oxidant under very mild conditions. The utility of our methodology was demonstrated by the C(sp 3 )–C(sp 3 ) bond cleavage in morpholine/piperazine arylamines with excellent functional group tolerance. Importantly, our methodology is noteworthy, not only in that it does not require any catalysts, but also in that it provides valuable possibilities for the scalable functionalization of clinical drugs and natural products.